Posterior Reversible Encephalopathy Syndrome in a Postpartum Preeclamptic Woman without Seizure - Ülkü Mete Ural; Gülsah Balik; Şenol Şentürk; Işık Üstüner; Uğur Çobanoğlu; Figen Kır Şahin (Case Reports in Obstetrics and Gynecology)
Posterior reversible encephalopathy syndrome (PRES) is a cliniconeuroradiological entity presenting with headache, confusion, visual disturbances or blindness, and seizures. Parieto-occipital white matter changes due to vasogenic oedema can be observed on imaging modalities. It rarely occurs without seizures and after delivery. We report a 33-year-old multigravida with a history of preeclampsia in term pregnancy complicated by PRES without seizures at the postpartum period. Clinical improvement with complete resolution without any complications was observed on the 6th day after delivery. Posterior reversible encephalopathy syndrome is reversible when early diagnosis is established and appropriate treatment is started without delay.